Design of smart food container using thermoelectric cooler and heat pipe integrated with internet of things - Adinda Diana Suci Istiqomah; Annisa Wulan Sari; Awaludin Martin (Prosiding SNTTM, 2025)
The increasing demand for food delivery systems that ensure product quality, freshness, and safety has driven the development of a Smart Food Container (SFC) integrated with Internet of Things (IoT) technology, utilizing a combination of Thermoelectric Cooler (TEC) and heat pipe as the primary temperature control mechanism. The design employs a TEC2-25408 module coupled with a copper heat pipe containing water as the working fluid, which efficiently transfers heat from the hot side of the TEC to maintain temperature stability while reducing the TEC’s workload. The integration of IoT technology using a NodeMCU ESP8266 enables real-time temperature monitoring and remote system control. The research process includes design, prototype fabrication, and experimental testing to evaluate system performance. The SFC prototype, with dimensions of 63 cm × 34 cm × 37 cm, consists of two compartments: a cooling section operating at 5–10 °C and a heating section operating at 50–70 °C. Based on experimental results indicate that the system achieves a design COP of 0.383 and an average experimental COP of 0.339 with a performance deviation of 11.38%.